2009
DOI: 10.1158/0008-5472.sabcs-09-1059
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain Is Associated with Increased Risk of Hot Flashes in Breast Cancer Survivors on Aromatase Inhibitors.

Abstract: Hot flashes in breast cancer survivors (BCS) receiving adjuvant aromatase inhibitor (AI) therapy are common, but risk factors for these symptoms are ill-defined. This study tested if body size is associated with hot flashes in BCS on AI therapy. A cross-sectional study of postmenopausal BCS receiving adjuvant AI therapy was performed. The primary outcome was occurrence of patientreported hot flashes. The primary exposures of interest were current body size and weight change since breast cancer diagnosis. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…One study reported weight gain as a ''bothersome'' symptom at 3 months by 14.7 % of women on AI compared to 6.3 % of cancer-free controls (p = 0.03); at 6 months, the proportions were 17.9 and 7.3 %, respectively (p = 0.004) [40]. In second study of women on AI therapy anywhere from 1 to 3 years, 27 % reported gaining more than 10 pounds, 61 % reported maintaining their weight, and 12 % reported losing weight [41]. In a third study (no information on how long the women were on an AI), 48.7 % reported weight gain-53 % of women whom had natural menopause compared to 43 % who had induced menopause [42].…”
Section: Ai Onlymentioning
confidence: 93%
“…One study reported weight gain as a ''bothersome'' symptom at 3 months by 14.7 % of women on AI compared to 6.3 % of cancer-free controls (p = 0.03); at 6 months, the proportions were 17.9 and 7.3 %, respectively (p = 0.004) [40]. In second study of women on AI therapy anywhere from 1 to 3 years, 27 % reported gaining more than 10 pounds, 61 % reported maintaining their weight, and 12 % reported losing weight [41]. In a third study (no information on how long the women were on an AI), 48.7 % reported weight gain-53 % of women whom had natural menopause compared to 43 % who had induced menopause [42].…”
Section: Ai Onlymentioning
confidence: 93%
“…1 AIs have been associated with worsening patient-reported outcomes (PROs), such as musculoskeletal symptoms and vasomotor symptoms. [2][3][4][5][6] One study demonstrated that 59% of women with early stage breast cancer who were receiving AIs experienced hot flashes, with 32% reporting moderate-to-severe hot flashes and 25% reporting significantly worsening hot flashes after the initiation of AI therapy. 6 The current treatments for AIassociated musculoskeletal and vasomotor symptoms are limited and may lead to drug discontinuation.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] One study demonstrated that 59% of women with early stage breast cancer who were receiving AIs experienced hot flashes, with 32% reporting moderate-to-severe hot flashes and 25% reporting significantly worsening hot flashes after the initiation of AI therapy. 6 The current treatments for AIassociated musculoskeletal and vasomotor symptoms are limited and may lead to drug discontinuation. Treatment for hot flashes include nonhormonal pharmacologic agents, such as clonidine, venlafaxine, gabapentin, and pregabalin; however, their use is limited because of suboptimal efficacy and potential side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating the patients’ perspective into the design of RCTs for acupuncture could inform study designs and facilitate recruitment efforts, thus increasing the probability of completing successful and definitive trials that produce reliable data. We conducted a qualitative study to identify attributes that influenced African American and Caucasian breast cancer survivors’ willingness to participate in clinical trials of acupuncture for hot flashes, a very common symptom affecting this population (17). …”
Section: Introductionmentioning
confidence: 99%